Sustainable Development in Teaching: Examining Puzzle-Based Instruction, Professional Success, and the Role of AI-Driven Education - Mehdi Manoochehrzadeh (Journal of English Language Teaching and Applied Linguistics, 2026)
Background: Recent scholarship emphasizes critical pedagogy and learner-centered approaches as cornerstones of sustainable ELT, aligning with UNESCO’s Education for Sustainable Development (ESD) goals. One promising pedagogical framework is Puzzle-Based Instruction (PBI), which engages learners through problem-solving, discovery, and critical thinkingAims: This study investigates the interplay between puzzle-based instruction (PBI), teachers’ professional success, and the integration of AI-driven educational tools as a catalyst for sustainable development in English language teaching (ELT). Specifically, it examines the prevalence and application of PBI principles among Iranian English language teachers (IELTs) in high schools and universities, alongside the extent to which learner-centered approaches are adopted in classroom practice.Methods: A stratified random sampling method was used to select 35 IELTs from diverse EFL contexts in Iran. Data were collected using two validated instruments: The inquiry-led puzzle teaching review (comprising five subsections and nine scenarios) and the Successful Iranian EFL Teacher Questionnaire (SIETQ), which encompasses 12 professional competence factors.Result: The study found a significant link between knowledge of PBI and professional success, with BA- and MA-level teachers showing lower awareness and engagement with socio-political content. It highlights the need for targeted professional development to improve PBI competence and critical thinking. Additionally, the research underscores the transformative potential of AI-driven education, like adaptive learning systems and automated feedback tools, to enhance reflective practice and support personalized instruction.Conclusion: Implications are offered for policymakers, curriculum designers, and teacher educators seeking to integrate both critical pedagogical and technological dimensions into ELT.